Utilization Sago Lees Fermentation of Different Levels For Growth of Baung (Mystus nemurus C.V) - David Sibarani; Indra Suharman; Adelina ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was conducted at experimental pond, Fisheries and MarineScience Faculty Riau University from February to April 2014. The aim of theresearch was to determine of utilization sago lees fermentation of different levelsthat provide the best growth of baung (mystus nemurus C.V). the experiment wastdesign by completely random design and student neuman keuls to differentiateamong treatments. The treatments were applied namely ( 0, 25, 50, 75, and100%). The result indicated that different levels of utilization sago leesfermentation doesn’t have significantly effect on growth of baung (Mystusnemurus C.V). The best result was achieved by treatment A ( Non – Sago leesfermentation). Total absolute body weight of 20,62 g, Spesific Growth Rate of1,82 % /day, food efficiency of 36,09 %, while the best protein retention andsurvival rate on treatment D ( 75 % of sago lees fermentation) of 11,34 % and 95% respectively. Water quality during the research are temperature of 27 – 31 0 C,pH of 5 – 6, and disolved oxygen of 4,5 - 5,4 ppm.Keyword : Fermentation, sago lees, growth, Mystus nemurus C.V